2021
DOI: 10.3171/2020.10.focus20402
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of subarachnoid Gd-based contrast agent accumulation: a potential complication of intraoperative MRI?

Abstract: OBJECTIVEIntraoperative MRI with Gd-based contrast agent (GBCA) improves the extent of resection of contrast-enhancing brain tumors. Signal changes of CSF due to perioperative GBCA leakage in the subarachnoid space have been reported. However, although GBCA potentially exhibits neurotoxic effects, so far no associated complications have been described. In this case series, the authors report a single-center cohort of patients with subarachnoid GBCA extravasation after intraoperative MRI and discuss potential n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Conventional GBCAs have been reported for their Gd-related accumulations and toxicities that have raised concerns and restricted their uses in compromised patients [ 16 , 19 , 20 , 23 , 75 , 76 ]. To understand the clearance profile of TPL-MDNPs, pharmacokinetic (PK) analysis of TPL-MDNPs was performed by measuring Mn concentration in blood plasma using inductively coupled plasma-optical emission spectrometry (ICP-OES) up to 24 h after a single injection of TPL-MDNPs (35.0 μmol Mn/kg) in healthy Sprague Dawley rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional GBCAs have been reported for their Gd-related accumulations and toxicities that have raised concerns and restricted their uses in compromised patients [ 16 , 19 , 20 , 23 , 75 , 76 ]. To understand the clearance profile of TPL-MDNPs, pharmacokinetic (PK) analysis of TPL-MDNPs was performed by measuring Mn concentration in blood plasma using inductively coupled plasma-optical emission spectrometry (ICP-OES) up to 24 h after a single injection of TPL-MDNPs (35.0 μmol Mn/kg) in healthy Sprague Dawley rats.…”
Section: Resultsmentioning
confidence: 99%
“…The Gd 3+ ion has unique paramagnetic properties which allow GBCAs to exhibit strong T1-weighted signal enhancement [ [16] , [17] , [18] ]. However, in recent years studies have revealed the release of free unchelated Gd 3+ ions from GBCAs, increasing Gd-toxicity and leading to undesirable depositions in sites such as the brain and bone [ 19 , 20 ]. Moreover, lanthanides such as Gd are primarily excreted from the body through glomerular filtration, which at times may lead to precipitation in tissues and major organs [ [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…У небольшого числа пациентов, у которых на иМРТ выявлено субарахноидальное скопление контраста или скопление контраста в резекционной полости, наблюдалась повышенная частота фокальных судорог и эпилептического статуса. У всех больных из этой группы хирурги отмечали повышенное кровоснабжение опухоли и проблемы в достижении гемостаза [24].…”
Section: оригинальная работаunclassified
“…16,17 Gd-based agents are the most prevalent commercial T 1 contrast agents in clinical studies. 18 However, more recently, the US Food and Drug Administration (FDA) has associated their application with several side effects, including nephrogenic systemic fibrosis (NSF), 19 free Gd 3+ accumulation in the human brain (gadolinium encephalopathy), 20 and limited blood circulation time. 21 On the other hand, Mn-based contrast agents have intrinsic disadvantages, such as neurodegenerative diseases caused by the toxicity of free Mn 2+ ions.…”
Section: Introductionmentioning
confidence: 99%